An Integrated Methodology for the Conservation and Management of Historic Parks: Theory and Practice - Alföldy, Gábor (4D Journal of Landscape Architecture and Garden Art, 2008)
In Hungary, there are fundamental faults in the field of conservation and management of história gardens today. This study States that lack of awareness towards história values, as well as incorrect detrition of priori tips, are generally greater issues than lack of money: spectacular results can be achieved through an integrated and holistic approach, even if there is no money available, at áll. This approach, which has already led to a great number of perfect and successful garden conservation projects as well as high-level maintenance all over the world, is completely unknown to most owners, managers, and designers of história gardens in this country.